Aquarium Monitoring System via IOT - Aman Shakirin Shamshulbahrin; Dr. Izanoordina Ahmad (Journal of Engineering Technology, 2022)
Aquarium monitoring system via IoT solves dead marine life issues such as prawns and fish. The system applies mobile apps "Blynk" and Arduino IDE link to the NodeMCU aquarium microcontroller. Microcontroller ESP8266 NodeMCU with right sensor type is used in water and connected to NodeMCU ESP8266. From this project, the project clearly demonstrates how end-users know the appropriate pH, temperature and water level. The dosing system developed in this system is ideal for use in any aquatic life, such as aquaculture for breeding or home aquarium. It will encourage users to prepare their aquarium maintenance, such as water change and filtering device. As for recommendation, an ammonia sensor will be used to improve the effectiveness and reliability of this project to monitor the nitrogen cycle in an aquarium.